2022
DOI: 10.1002/advs.202104855
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance and Reliable White Organic Light‐Emitting Fibers for Truly Wearable Textile Displays

Abstract: Light‐emitting fibers have been intensively developed for the realization of textile displays and various lighting applications, as promising free‐form electronics with outstanding interconnectivity. These advances in the fiber displays have been made possible by the successful implementation of the core technologies of conventional displays, including high optoelectronic performance and essential elements, in the fiber form‐factor. However, although white organic light‐emitting diodes (WOLEDs), as a fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Wearable electronic devices are attracting more and more attention as they can provide personal real-time medical monitoring, communication, entertainment interaction, etc. Textiles are considered as an ideal platform to integrate electronics for wearable applications due to their lightweight, softness, and comfort. There have been many studies on fabric/fiber-based electronic devices, including sensors, nanogenerators, heaters, solar cells, batteries, etc. Light emission is another interesting functionality that can be integrated with textiles for applications in wearable display, fashion design, warning clothing, and light therapy. , So far, various luminescence strategies, such as alternating current electroluminescence (ACEL), organic light-emitting diodes (OLED), light electrochemical cells (LECs), and side-emitting polymeric optical fibers (POFs) coupled with LEDs, have been developed for fabricating light-emitting devices on fibers or planar fabrics. Stretchability, washability, large display area, and low production cost are the fundamental requirements for light-emitting textiles from a practical standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable electronic devices are attracting more and more attention as they can provide personal real-time medical monitoring, communication, entertainment interaction, etc. Textiles are considered as an ideal platform to integrate electronics for wearable applications due to their lightweight, softness, and comfort. There have been many studies on fabric/fiber-based electronic devices, including sensors, nanogenerators, heaters, solar cells, batteries, etc. Light emission is another interesting functionality that can be integrated with textiles for applications in wearable display, fashion design, warning clothing, and light therapy. , So far, various luminescence strategies, such as alternating current electroluminescence (ACEL), organic light-emitting diodes (OLED), light electrochemical cells (LECs), and side-emitting polymeric optical fibers (POFs) coupled with LEDs, have been developed for fabricating light-emitting devices on fibers or planar fabrics. Stretchability, washability, large display area, and low production cost are the fundamental requirements for light-emitting textiles from a practical standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…However, although white organic light‐emitting diodes (WOLEDs) are essential to full‐color displays and solid‐state lighting, fiber versions have remained largely undeveloped because of the complexity of the WOLED structures. In 2022, Hwang et al reported the first fiber‐based WOLEDs (fiber WOLEDs), demonstrating that WOLEDs with a single white EML can be successfully introduced on fiber using the dip‐coating method, simulation, and optimized processes 46 . The fiber WOLEDs featured a dip‐coatable single white EML that was composed of RGB hosts and RGB dopants; PVK, 26DCzppy, TPBi, Hex‐Ir(phq) 2 acac, Ir(ppy) 3 , and Ir(Fppy) 3 .…”
Section: Organic Light‐emitting Fibers For Textile Displaysmentioning
confidence: 99%
“…In 2022, Hwang et al reported the first fiber-based WOLEDs (fiber WOLEDs), demonstrating that WOLEDs with a single white EML can be successfully introduced on fiber using the dipcoating method, simulation, and optimized processes. 46 The fiber WOLEDs featured a dip-coatable single white EML that was composed of RGB hosts and RGB dopants; PVK, 26DCzppy, TPBi, Hex-Ir(phq) 2 acac, Ir(ppy) 3 , and Ir(Fppy) 3 . To achieve a reliable color index and implement high-performance WOLEDs on fiber, the dominant point of energy transfer (ET) in the white EML was determined by optimizing the RGB ratio using simulations and experiments.…”
Section: Fiber-based Display Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, not only for simple one-dimensional information transmission from devices to human, but to transmit information among people and devices in both directions for various purposes, display technology has achieved form-factor innovation into various kinds of smart devices, especially into wearable displays. Among such innovations, clothing-type displays are attracting attention as very effective intercommunication methods for communication among humans and devices, and the most human-friendly technology suitable for the movements of the human body [1][2][3][4][5][6][7] . Moreover, clothing-type displays are state-of-the-art technology including multi-functionality and aesthetics at the same time, applicable to numerous application elds such as smart textiles, military goods, and automobile interior walls [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%